A sulfonated polymer membrane with Ag-based graft: morphology, characterization, antimicrobial activity and interception ability. Issue 59 (26th July 2017) - He, Qi; Zhu, Zipei; Dong, Hao; Xiao, Kaijun
Abstract : Ag-based nano-graft can impart broad-spectrum antimicrobial activity to a polymer membrane and enhance its anti-fouling capacity effectively. Abstract : Ag-based nano-graft is a common approach used to impart broad-spectrum antimicrobial activity to a polymer membrane. The primary problem with this approach is low compatibility between the grafted particles and the polymer main-body, followed by its low anti-adhesion for undesired membrane fouling. To overcome these problems, this study functionalized polyethersulfone (PES) materials by a sulfonation process to form the membrane backbone. FTIR, thermogravimetry (TG) and contact angle (CA) analysis showed that sulfonate treatment improved hydrophilicity and surface activity. Accordingly, the Ag-based nano-grafts were embedded on the membrane by immersing into a Ag + solution and then reducing. The resulting membrane was characterized by a series of assays. SEM and AFM scans were used to examine the membrane surface for Ag nanoparticles (AgNPs) distribution. XRD and XPS analysis determined the AgNPs state. A concentration assay revealed that the Ag release from the membrane was maintained within the safety range during the filtration process. An antimicrobial ring test showed the antimicrobial activities of the membrane for different microbial strains. BET analysis and the water-absorption test analyzed the porosity properties of the membrane. The filtration performance assay proved that the membrane had remarkable interception ability for various solutes. Consequently, it showed that the prepared SPES-AgNPs membrane will have a promising application as an antimicrobial filtration membrane for water treatment.